2020
DOI: 10.1002/tox.22986
|View full text |Cite
|
Sign up to set email alerts
|

Antimycin A shows selective antiproliferation to oral cancer cells by oxidative stress‐mediated apoptosis and DNA damage

Abstract: The antibiotic antimycin A (AMA) is commonly used as an inhibitor for the electron transport chain but its application in anticancer studies is rare. Recently, the repurposing use of AMA in antiproliferation of several cancer cell types has been reported. However, it is rarely investigated in oral cancer cells. The purpose of this study is to investigate the selective antiproliferation ability of AMA treatment on oral cancer cells. Cell viability, flow cytometry, and western blotting were applied to explore it… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 55 publications
0
9
0
Order By: Relevance
“…It has been also identified as target for anticancer drugs. Antimycin A is the most classic CIII inhibitor to trigger apoptosis for effectively eliminating cancer cells [ 263 , 264 ]. Resveratrol, a plant-derived polyphenol, exhibited considerable antitumor efficacy by efficiently inhibiting ETC complexes, especially CIII to induce apoptosis and disturb multiple cellular processes in primary and resistant cancer cells [ 265 – 267 ].…”
Section: Targeting Mitochondria To Overcome Cancer Drug Resistance: T...mentioning
confidence: 99%
“…It has been also identified as target for anticancer drugs. Antimycin A is the most classic CIII inhibitor to trigger apoptosis for effectively eliminating cancer cells [ 263 , 264 ]. Resveratrol, a plant-derived polyphenol, exhibited considerable antitumor efficacy by efficiently inhibiting ETC complexes, especially CIII to induce apoptosis and disturb multiple cellular processes in primary and resistant cancer cells [ 265 – 267 ].…”
Section: Targeting Mitochondria To Overcome Cancer Drug Resistance: T...mentioning
confidence: 99%
“…In the present study, we found that AA or ACR could induce G0/G1 phase arrest in both PC12 cells and SK‐N‐SH cells, interestingly they caused significant different phase decreases in the PC12 and SK‐N‐SH cells, G2/M phase and S phase, respectively. Even the same reagent may induce different cell cycle arrest responses in different cells 44 . ACR was a water solubility monomer that could be easily entered the body and even could effectively traverse the blood–brain barrier and the placental barrier 28,45–47 .…”
Section: Discussionmentioning
confidence: 99%
“…ACR could directly combine with the cellular antioxidant biomarker GSH, decrease the GSH content, disturb the intracellular redox balance and cause ROS accumulation 47 . ROS could generate DNA damage involving 8‐OHdG and DNA double‐strand breaks, and even cause apoptosis 39,44,49 . ACR was reported to generate genotoxicity through depletion of GSH causing intracellular ROS to induce oxidative DNA damage 50 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, azoxystrobin, an inhibitor of complex III, could suppress cell proliferation and cause MAP of OSCC cells by promoting mtROS formation [ 13 ]. In addition, antimycin A, another inhibitor of complex III, could also lead to the MAP of OSCC cells by inducing the production of mtROS [ 84 ]. Interestingly, ROS can influence Bcl-2 family proteins by regulating their phosphorylation and ubiquitination through many signaling pathways [ 85 , 86 ].…”
Section: Mitochondrial-targeted Therapeutic Strategies For Osccmentioning
confidence: 99%